On the Other Side: Manipulating the Immune Checkpoint Landscape of Dendritic Cells to Enhance Cancer Immunotherapy - Kong, Benjamin Y.; Bolton, Holly; Kim, Julius W.; Silveira, Pablo A.; Fromm, Phillip D.; Clark, Georgina J. (Frontiers in Oncology, 2019)
Monoclonal antibodies targeting co-inhibitory immune checkpoint molecules have been successful in clinical trials of both solid and haematological malignancies as acknowledged by the 2018 Nobel Prize in Medicine, however improving clinical response rates is now key to expanding their efficacy in areas of unmet medical need. Antibodies to checkpoint inhibitors target molecules on either T cells or tumour cells to stimulate T cells or remove tumour mediated immunosuppression respectively. However, many of the well characterised T cell immune checkpoint receptors have their ligands on antigen presenting cells or exert direct effects on those cells. Dendritic cells are the most powerful antigen presenting cells; they possess the ability to elicit antigen-specific responses and have important roles in regulation of immune tolerance. Despite their theoretical benefits in cancer immunotherapy, the translation of DC therapies into the clinic is yet to be fully realised and combining DC-based immunotherapy with immune checkpoint inhibitors is an attractive strategy. This combination takes advantage of the antigen presenting capability of DC to maximise specific immune responses to tumour antigens whilst removing tumour-associated immune inhibitory mechanisms with immune checkpoint inhibition. Here we review the expression and functional effects of immune checkpoint molecules on DC and identify rational combinations for DC vaccination to enhance antigen-specific T cell responses, cytokine production and promotion of long-lasting immunological memory.